Patterns of Relationships between Cardiovascular Disease Risk Factors and Neurocognitive Function in African Americans - Sims, Regina (2008)
OBJECTIVE: The association between cardiovascular disease (CVD) risk and neurocognitive function has gathered a good deal of attention in the health and social science literature; however, the relationship among several CVD risk factors and neurocognitive function has not been fully explored in an African American sample. The purpose of this study was to examine the pattern of relationships among four CVD risk factors and five measures of higher cortical functions. METHODS: Data were collected from a sample of 106 African American community-dwelling adults in the metropolitan Washington, DC, area. A nurse collected blood pressure, waist circumference, and a blood sample (to assess triglycerides and high-density lipoprotein (HDL) cholesterol) from study participants. Participants completed the Symbol Digit Modalities Test, Trailmaking B, Stroop Colorword Task, California Verbal Learning Test-II, and Wisconsin Card Sorting Test as assessments of neurocognitive function. Canonical analysis and multiple regression analysis were the major statistical methods utilized to assess relationships between CVD risk factors and neurocognitive function. RESULTS: The results suggest that 1) attentional processes are associated with diastolic blood pressure levels, 2) verbal learning processes are associated with diastolic blood pressure and triglyceride levels, and 3) the ability to shift cognitive set is associated with HDL cholesterol levels. CONCLUSION: As cardiovascular health worsens in our society, particularly among ethnic minorities, the neurocognitive consequences must be clearly understood. Future studies should focus on identifying and building awareness of cardiovascular and neurocognitive links through longitudinal research designs and brain imaging technology.